Tourism and COVID-19: Changes in Travel and Behavioral Patterns of Residents of Bosnia and Herzegovina - ČAUŠEVIĆ, Amra (Journal of Environmental Management and Tourism, 2023)
This paper analyses whether there have been any changes in the behavior and patterns of tourist travel after the outbreak of the COVID-19 pandemic. The convenience sample included 265 respondents. The results of the study show that the most important factors in choosing to travel during the COVID-19 pandemic are: cleanliness, safety, comfort, costs, and social distance. The results of the study show a statistically significant difference in the factors that influence choosing to travel during COVID-19 with regard to employment, i.e. , occupation, whereby the most factors when deciding on travel during COVID-19 are considered by pensioners and the least by students. When choosing a destination, as well as the image of the destination from the perspective of tourists, the study showed that owning a car is a statistically significant factor. The study also shows that there is a positive relationship that is statistically significant between the factors that influence choosing to travel during COVID-19 and the factors when choosing a destination from the perspective of tourists and the image of the destination, so those respondents who take into account more factors when choosing to travel during COVID-19, also take into account several factors when choosing a destination from the perspective of tourists and the image of the destination.